THE EFFECT OF USING CUE CARDS ON STUDENTS’ VOCABULARY MASTERY AT SEVENTH GRADE STUDENTS OF SMP N 16 MANDAU - setiawati, setiawati (AL-ISHLAH: Jurnal Pendidikan, 2018)
Abstract: This study aimed to know The Effect of Using Cue Cards on Students’ Vocabulary Mastery at Seventh Grade Students of SMP N 16 Mandau. Related to the object of the research, the researcher used Pre - experimental method. The design of the research used pre test/ post test design. The research was conducted at Seventh Grade students of SMP N 16 Mandau. The population of this research was the seventh grade students of SMP N 16 Mandau. The sample of the research was 30 students. In analyzing the research data, the researcher used Paired sample T-Test by using SPSS. The data were taken from students’ English achievement pre test and post test score. Based on statistical calculation in data analysis, the researcher gave interpretation of pre test and post test score. From the calculation, t obtained was 10.343, the level significance of 5% was 2.05, and the level of significance 1% was 2.76. it showed 2.05>10.343>2.76. It could be concluded that alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. It means that there was significant effect of using cue cards on students’ vocabulary mastery at seventh grade students of SMP N 16 Mandau.Key words: Cue cards, Vocabulary mastery